Nuraga Sanubari Musical Composition | Komposisi Karawitan Nuraga Sanubari - I Komang Galang Widnyana (GHURNITA: Jurnal Seni Karawitan, 2024)
Nuraga Sanubari is based on musical art, which has the background of the author's desire to create relaxation music that utilizes traditional instruments because, currently, the processing of relaxation music usually tends to use Western instruments. The author wants to express his feelings through musical works to be listened to and distributed to the general public. The spoken media used are as follows, flute gambuh, gumanak, kempur gambuh, gentorag, dun-dun, and Native American Flute. In creating this musical work, the arranger used the method from Alma M. Hawkins in the book Creating Through Dance (1964), which explains that the arranger went through 3 stages: Exploration, Improvisation and Forming. This relaxation music piece has two parts. In the first part, the author wants to emphasize further the tonal character of the gambuh flute, which is combined with the native American flute, and in the second part, the author creates a happy and happy atmosphere by processing the dun-dun, kempur, gumanak, and gentorag instruments. The number of musicians in this relaxation music work is 17 people including the author, and the duration of the work is approximately 11 minutes.